PRKAA/AMPK restricts HBV replication through promotion of autophagic degradation. Issue 9 (1st September 2016) - Xie, Na; Yuan, Kefei; Zhou, Li; Wang, Kui; Chen, Hai-Ning; Lei, Yunlong; Lan, Jiang; Pu, Qinqin; Gao, Wei; Zhang, Lu; Shen, Guobo; Li, Qifu; et al.
ABSTRACT: Adenosine monophosphate-activated protein kinase (AMPK) is a crucial energy sensor that maintains cellular energy homeostasis. AMPK plays a critical role in macroautophagy/autophagy, and autophagy facilitates hepatitis B virus (HBV) replication. To date, the intrinsic link among AMPK, autophagy and HBV production remains to be elucidated. Here, we demonstrate that PRKAA (a catalytic subunit of AMPK) is activated in response to HBV-induced oxidative stress, which in turn decreases the production of HBV. Mechanistic studies reveal that the autophagy machinery is associated with the inhibitory effect of PRKAA/AMPK on HBV production. Activation of PRKAA/AMPK promotes autolysosome-dependent degradation through stimulation of cellular ATP levels, which then leads to the depletion of autophagic vacuoles. Taken together, our data suggest that the activation of AMPK might be a stress response of host cells to restrict virus production through promotion of autophagic degradation. These findings therefore indicate that AMPK could provide a potential therapeutic target for HBV infection.